2018
DOI: 10.1080/14786419.2018.1446014
|View full text |Cite
|
Sign up to set email alerts
|

Nigericin and grisorixin methyl ester from the Algerian soil-living Streptomyces youssoufiensis SF10 strain: a computational study on their epimeric structures and evaluation of glioblastoma stem cells growth inhibition

Abstract: The present work describes the metabolites produced by a strain identified as Streptomyces youssoufiensis, whose secondary metabolites profile has not been studied so far. The crude ethyl acetate extract was analyzed by high performance liquid chromatography-electrospray ionization mass spectrometry, leading to the detection of the ionophoric polyethers nigericin, epinigericin, abierixin and the newly isolated grisorixin methyl ester. The presence of epimeric forms of nigericin/epinigericin and grisorixin/epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[91]. A series of polyether antibiotics including nigericin (40), epinigericin (41), abierixin (42), and the new grisorixin methyl ester (43) were isolated from the Streptomyces youssoufiensis SF10 strain collected from Chélia Mountain, in Khenchela (North-eastern Algeria) [105]. The online coupled HPLC-ESIMS analysis provided the full polyether profile, and the preparative HPLC technique in the reversed phase condition gave pure compounds, which were identified by extensive NMR and ESI-MS spectra in comparison with reported data.…”
Section: Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[91]. A series of polyether antibiotics including nigericin (40), epinigericin (41), abierixin (42), and the new grisorixin methyl ester (43) were isolated from the Streptomyces youssoufiensis SF10 strain collected from Chélia Mountain, in Khenchela (North-eastern Algeria) [105]. The online coupled HPLC-ESIMS analysis provided the full polyether profile, and the preparative HPLC technique in the reversed phase condition gave pure compounds, which were identified by extensive NMR and ESI-MS spectra in comparison with reported data.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Recently, the polyether antibiotics nigericin (40) and the new grisorixin methyl ester (43) isolated from Streptomyces youssoufiensis SF10 have provided significant cytotoxic activities against glioblastoma stem cells, with a higher activity for grisorixin methyl ester (GI 50 values of 3.85 and 3.05 µM for two human glioblastoma stem cell lines), corresponding to a higher growth-inhibion cell-proliferation than the drug temozolomide [105]. The data are remarkable due to both the nature of glioblastoma multiforme as the most malignant primary brain tumors and the effect against stem cells which are resistant to the conventional therapies.…”
Section: Tumor Cells Growth Inhibitorsmentioning
confidence: 99%
“…A detection limit corresponding to 1 µg/mL (1.38 µM) was also determined. Using a sample of pure nigericin previously isolated by the same SF10 strain [23], a calibration curve was constructed by plotting the ELSD response area versus nigericin concentration. The obtained calibration curve presented a very good linear fit (Figure 2).…”
Section: Quantitative Methods For Nigericin Evaluationmentioning
confidence: 99%
“…The ionophoric polyethers nigericin, epinigericin, abierixin and the newly isolated grisorixin methyl ester were isolated in pure form from the crude ethyl acetate extract, and their structures were fully characterized by mass spectrometry and extensive NMR analysis. Furthermore, we observed that both nigericin and grisorixin methyl ester affected human glioblastoma stem cell proliferation in a dose-dependent manner, with promising GI 50 values compared with the currently used drug, temozolomide [23].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation